Analisis reaksi saham bank umum terhadap perusahaan foreign exchange system di pasar modal Indonesia - Kusnanto, Amir (Akutansi Bisnis & Manajemen ( ABM ), 2004)
Tes jadi invite investigated the reaction of stock price and trading volume listen komersial Banks to to the change in exchange red regim from manage to Freed system. Data exploid form jsx database using proposive sampling 24 off-31 Banks are selected as simple of Study base open to kriteria, period of listing and list thing status. Period before much 1997 and no record of the listing status over the observation period are finally selected using one and parared samplete this to defence there is not signifikan difference on arr Before and After The period of Change in exchange red regiments. Where as for everage trading volume activity there is a significantly different between Before and After the change in exchange red system